IDENTIFICATION OF THE PARAMETERS OF THE COMPLEX ORE THERMAL FURNACE MODEL AND ITS ADEQUACY (Modern Problems of Metallurgy, 2023)
Previously, the development of an algorithmic model of the operation of an ore-thermal furnace was considered, which takes into account the specifics of electrical, thermal and chemical processes that are directly interconnected when producing ferroalloys. The versatility of this algorithm lies in the possibility, depending on the set goals, of interrupting the cycle of calculations in the subsequent determination of either the amount of spent electrical energy (total and current), or the formed melt (also total and current), or something else. The model is adjusted according to the physical parameters of the charge, such as: - specific electrical resistance; - mass heat capacity; - specific density; - thermal conductivity coefficient. Their values have their limits of fluctuation depending on the temperature. Given the above, it is very difficult to obtain the latter for each specific melt. Therefore, it is suggested to search for them by solving the computational optimization problem based on the results of the performed fusions. The use of computational identification provides another significant advantage - the ability to establish the structural inadequacy of the model. To implement the proposed identification method, it is necessary to pre-set the intervals within which the desired parameters are found with sufficient probability. It is obvious that they can be determined based on already available information. At the beginning of this experiment, the number of intervals is selected for dividing the parameter values in their predefined ranges and the corresponding data arrays are created. Next, the first combination is selected and all the necessary calculations are carried out on the simulation mathematical model of the ore-thermal furnace, the results of which are compared with the real values obtained at the facility and the forecast error is calculated. Then another combination of parameter values is taken and the same calculations are performed. Then, in the same way, all possible variants of values are enumerated. After the end of the sorting cycle, the values of all parameters are displayed for which the minimum calculation error was obtained. If the latter is acceptable from the point of view of research, then it is considered that the combination of values of the model setting parameters is found, namely the model is adequate to the process. And this, in turn, makes it possible to use it for further computational calculations. The identification of the parameters of the complex model of the ore-thermal furnace by solving the optimization problem regarding the value of its root mean square error of the forecast at all possible values of these parameters within the permissible limits allows to simultaneously determine the structural and parametric adequacy of the model itself.
Keywords: ore-thermal furnace; charge parameters; ferroalloys; algorithmic model; optimization problem.